Venom alkaloids against Chagas disease parasite: search for effective therapies - Silva, Rafael C. M. Costa (2020)
Chagas disease is an important disease affecting millions of patients in the New World and is caused by a protozoan transmitted by haematophagous kissing bugs. It can be treated with drugs during the early acute phase; however, effective therapy against the chronic form of Chagas disease has yet to be discovered and developed. We herein tested the activity of solenopsin alkaloids extracted from two species of fire ants against the protozoan parasite Trypanosoma cruzi, the aetiologic agent of Chagas disease. Although IC50 determinations showed that solenopsins are more toxic to the parasite than benznidazole, the drug of choice for Chagas disease treatment, the ant alkaloids presented a lower selectivity index. As a result of exposure to the alkaloids, the parasites became swollen and rounded in shape, with hypertrophied contractile vacuoles and intense cytoplasmic vacuolization, possibly resulting in osmotic stress; no accumulation of multiple kinetoplasts and/or nuclei was detected. Overexpressing phosphatidylinositol 3-kinase—an enzyme essential for osmoregulation that is a known target of solenopsins in mammalian cells—did not prevent swelling and vacuolization, nor did it counteract the toxic effects of alkaloids on the parasites. Additional experimental results suggested that solenopsins induced a type of autophagic and programmed cell death in T. cruzi. Solenopsins also reduced the intracellular proliferation of T. cruzi amastigotes in infected macrophages in a concentration-dependent manner and demonstrated activity against Trypanosoma brucei rhodesiense bloodstream forms, which is another important aetiological kinetoplastid parasite. The results suggest the potential of solenopsins as novel natural drugs against neglected parasitic diseases caused by kinetoplastids.